2001
DOI: 10.1093/nar/29.10.2052
|View full text |Cite
|
Sign up to set email alerts
|

UV induces nucleolar translocation of ING1 through two distinct nucleolar targeting sequences

Abstract: The ING1 candidate tumor suppressor is downregulated in a variety of primary tumors and established cancer cell lines. Blocking its expression experimentally promotes unregulated growth in vitro and in vivo, using cell and animal models. Alternative splicing products encode proteins that localize to the nucleus, inhibit cell cycle progression and affect apoptosis in different model systems. Here we show that ING1 proteins translocate to the nucleolus 12-48 h after UV-induced DNA damage. When a small 50 amino a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
104
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(109 citation statements)
references
References 29 publications
5
104
0
Order By: Relevance
“…The characteristic nucleolar localization of p14ARF or p19ARF was not affected by the levels of p33ING1 in any case (compare middle and bottom panels in Figure 2a, c and e). It is worth mentioning that a similar accumulation of p33ING1 in nucleoli has been described to occur in human diploid fibroblasts upon exposure to high doses of UV radiation (Scott et al, 2001a). In that study, mutant versions of the p33ING1 protein that did not relocalize in the nucleolus showed a reduced ability to induce apoptosis.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…The characteristic nucleolar localization of p14ARF or p19ARF was not affected by the levels of p33ING1 in any case (compare middle and bottom panels in Figure 2a, c and e). It is worth mentioning that a similar accumulation of p33ING1 in nucleoli has been described to occur in human diploid fibroblasts upon exposure to high doses of UV radiation (Scott et al, 2001a). In that study, mutant versions of the p33ING1 protein that did not relocalize in the nucleolus showed a reduced ability to induce apoptosis.…”
supporting
confidence: 66%
“…In this regard, recent reports show that ARF plays an important role in ribosomal biogenesis, in the nucleolus (Itahana et al, 2003;Sugimoto et al, 2003;Bertwistle et al, 2004). As p33ING1 can also accumulate in the nucleolus (Figure 2; see also Scott et al, 2001a), a possible functional connection at this level is possible. More importantly, there is ample evidence, both in mammals and yeast, showing that ING proteins can form complexes with histone deacetylases and histone acetyltransferases.…”
mentioning
confidence: 77%
“…By looking for sequential similarities between the hLa-NoLS described here and other published sequences mediating nucleolar localization of different human proteins (45)(46)(47)(48)(49)(50)(51)(75)(76)(77)(78), we aligned those sequences with the hLa-NoLS (Fig. 4C).…”
Section: Discussionmentioning
confidence: 99%
“…Because elements for nucleolar localization have been described for other proteins (45)(46)(47)(48)(49)(50)(51)(52), it is conceivable to assume that hLa bears such a signal to ensure its interaction with pre-tRNAs, for example, in the nucleolus besides the binding of pre-U3 snoRNA or U6 snRNA in the nucleoplasm. In this report we identified a yet unknown nucleolar localization signal (NoLS) in the C-terminal region of hLa, and we show that it functions in a heterologous context.…”
mentioning
confidence: 99%
“…Overexpression of DEDD, for instance, can make this protein to translocate to the nucleus (Schickling et al, 2001) as associated with caspase 8/10 (Alcivar et al, 2003) and to co-localize with UBF in the nucleolus; since in vitro DEDD is capable of inhibiting transcription, this suggests that DEDD might be involved in shutting-off the cell biosynthetic activities. Several other nuclear and nucleolar proteins have been reported to move to ectopic locations during apoptosis; among them, B23 was found to translocate from the nucleolus to the nucleoplasm in daunomycin-induced apoptosis (Chan and Chan, 1999), while the candidate tumor suppressor protein, ING1 moves the nucleolus and this translocation may facilitate apoptosis in UV-treated cells (Scott et al, 2001). Martelli et al (2000) reported that some nucleolar antigens (namely, PARP-1 and UBF) are cleaved during apoptosis, whereas others (fibrillarin, B23 and C23) are not; cleavage of topoisomerase I and B23 has been shown to occur in cis-DDP-induced apoptosis (Horky et al, 2001).…”
Section: Nucleoplasmic and Nucleolar Rnps In Apoptosismentioning
confidence: 99%